Aptamers: precision tools for diagnosing and treating infectious diseases - Sujith, Swathi; Naresh, Rajalakshmi; Srivisanth, B. U.; Sajeevan, Anusree; Rajaramon, Shobana; David, Helma; Solomon, Adline Princy (Frontiers in Cellular and Infection Microbiology, 2024)
Infectious diseases represent a significant global health challenge, with bacteria, fungi, viruses, and parasitic protozoa being significant causative agents. The shared symptoms among diseases and the emergence of new pathogen variations make diagnosis and treatment complex. Conventional diagnostic methods are laborious and intricate, underscoring the need for rapid, accurate techniques. Aptamer-based technologies offer a promising solution, as they are cost-effective, sensitive, specific, and convenient for molecular disease diagnosis. Aptamers, which are single-stranded RNA or DNA sequences, serve as nucleotide equivalents of monoclonal antibodies, displaying high specificity and affinity for target molecules. They are structurally robust, allowing for long-term storage without substantial activity loss. Aptamers find applications in diverse fields such as drug screening, material science, and environmental monitoring. In biomedicine, they are extensively studied for biomarker detection, diagnostics, imaging, and targeted therapy. This comprehensive review focuses on the utility of aptamers in managing infectious diseases, particularly in the realms of diagnostics and therapeutics.